2004
DOI: 10.1021/ie030611a
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Pulping from Tagasaste (Chamaecytisus proliferusL.F. ssp palmensis). A New Promising Source for Cellulose Pulp

Abstract: The chemical characteristics of tagasaste trimming wood and eucalyptus wood are similar in ash, holocellulose, lignine, xylan, and acetyl groups. Then, tagasaste wood could be an adequate raw material for pulp and paper making. Therefore, the influence of independent variables in the pulp processing of tagasaste with ethanol-water mixtures (ethanol concentration, time, pulping temperature, wash temperature, and disintegrate temperature) on various properties of the pulp (yield, kappa number, viscosity, brightn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 The monosaccharides (glucose, xylose and arabinose) and acetic acid contained in hydrolysates were determined by HPLC in order to estimate (after corrections for stoichiometry and sugar decomposition) the cellulose (as glucan), hemicelluloses (as xylan), and acetyl group contents (Díaz et al, 2004). Chromatographic runs were done with an Agilent 1100 HPLC instrument equipped with an Aminex HPX-87H column packed with ion-exchange resin under the following conditions: mobile phase, sulphuric acid at 0.05 mol·L -1 ; flow rate, 0.6 mL·min -1 ; column temperature, 30°C; injected volume, 20 μL.…”
Section: Source and Analysis Of Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 The monosaccharides (glucose, xylose and arabinose) and acetic acid contained in hydrolysates were determined by HPLC in order to estimate (after corrections for stoichiometry and sugar decomposition) the cellulose (as glucan), hemicelluloses (as xylan), and acetyl group contents (Díaz et al, 2004). Chromatographic runs were done with an Agilent 1100 HPLC instrument equipped with an Aminex HPX-87H column packed with ion-exchange resin under the following conditions: mobile phase, sulphuric acid at 0.05 mol·L -1 ; flow rate, 0.6 mL·min -1 ; column temperature, 30°C; injected volume, 20 μL.…”
Section: Source and Analysis Of Biomassmentioning
confidence: 99%
“…The solid residue after hydrolysis was recovered by filtration through a 0.45 ?m filter and considered as Klason lignin. .....order to estimate (after corrections for stoichiometry and sugar decomposition) the cellulose (as glucan), hemicelluloses (as xylan), and acetyl group contents (Díaz et al, 2004). ....…”
mentioning
confidence: 99%
“…Historically, the organosolv process has been investigated largely from the perspective of paper production (Diaz et al, 2004;Gilarranz et al, 1998;Jimenez et al, 2004;van Heiningen, 1996, 1997), but several studies have also involved analysis of the lignin fraction extracted during pulping (Hepditch and Thring, 1997;Liu et al, 2000;Lora et al, 1993), including demonstration of its potential for manufacture of various industrial co-products such as adhesives or biodegradable polymers (Boocock and Balatinecz, 1992;Kubo and Kadla, 2004;Thring et al, 1997). Generation of high-quality lignin and other potentially valuable co-products (e.g., furfural and acetic acid) from woody feedstocks may be critical to otherwise marginally cost-effective biorefinery schemes for fuel ethanol production (Pan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, this process involved treating wood chips with a mixture of water, an organic solvent, and a catalyst at approximately 200°C and 400 psi resulting in delignification of the lignocellulosic biomass through the cleavage of lignin-carbohydrate bonds, ligninlignin bonds, and the solubilization of the lignin in the organic solvent [8,9]. Although most of these earlier investigations relate to the pulp and paper applications of the organosolv process [10], the need for alternatives to fossil-based transportation fuels has renewed interest in its application as a pretreatment that produces a lignocellulosic substrate, which is readily hydrolyzed by cellulases [11]. Previous research in our laboratory has shown that the hydrolysis of organosolv pretreated LPP [5] resulted in greater amounts of glucose conversion than did steam pretreated LPP at equivalent enzyme activity loadings (20 filter paper units or FPU per gram cellulose) [12].…”
mentioning
confidence: 99%